Prosedur Pemeriksaan MRI Leher pada Kasus Karsinoma Nasofaring di Instalasi Radiologi RS Ken Saras Kabupaten Semarang - Yeti Kartikasari; Emi Murniati; Muhammad Sakur (Jurnal Imejing Diagnostik (JImeD), 2021)
Background: Magnetic Resonance Imaging (MRI) is a diagnostic imaging modality that can generate slices anatomy body multiplanar by contrast in a very good resolution. The results of the  of an MRI description is more accurate for diagnosing Carcinoma of the nasopharynx. On examination of of the neck MRI  with the case of carcinoma, after infusion of contrast Moeller and Reif (2003) suggested to use T1 TSE Coronal and axial sequence  and using the 4 mm slice thickness , but in Radiology instalation of  Ken Saras Hospital using  T1 and T1 TSE TSE Fat Saturation Coronal, sagittal and axial sequence as well as using slice thickness 2 mm in axial slices. The purpose of this research is to know the procedure of examination of of the neck MRI  in the case of Carcinoma of the nasopharynx, justifying  T1 Fat Saturation sequence after infusion media kontaras and reasons of  wearing slice thickness 2 mm in axial slices.Methods: This type of research is qualitative research with case studies approach. Data retrieval is done by  observation, documentation, interviews with two specialists in radiology, 2 radiografer and 1 doctor who send the patient.  The data obtained  analized  by using the table  categorisation and coding.Result: The results of the research showed that MRI examination procedure of the neck in the case of Carcinoma of nasopharynx in Radiology Installation of  Ken Saras hospital using  T1 TSE multi planar (coronal, sagittal and axial), T2 TSE multi planar and T2 TSE Fat Saturation multi planar sequences before infusion of contrast media,  T1 and T1 TSE TSE Fat Saturation multi planar sequences after infusion contrast and using the slice thickness 2 mm in axial slices. Addition sequence T1 TSE Fat Saturation after infusion of contrast aimed to clarify the limits of the tumor with surrounding tissue and image of  Lymphadenopathy.Conclusion: While using 2 mm slice thickness  in axial slices aims to show the abnormalities or nodules-small nodules on the nasopharynx and to see the expansion Stadium in the  surrounding area of the nasopharynx.